In the Language of Their Hearts: Emotions and Language Choice in Child-Parent Interaction, Insights from a Yupik village - Morgounova Schwalbe, Daria (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
In studies of language choice and minority language shift and maintenance, attention is frequently given to factors other than emotions: social context of contact, language politics, linguistic competence and attitudes, educational policies, and political agendas in a society. Yet human language is ideologically saturated, aesthetically experienced empirical phenomena, characterized by complex dynamics and linked to group and personal identities, morality, aesthetics, and epistemology. While negative moral emotions (e.g., shame) may lead people to abandon their first language, heritage languages may still be perceived as “more emotional,” and their loss and maintenance is a deeply emotional matter. Drawing on Pavlenko, Cavanaugh, and Ahmed, I discuss the role of emotion-related factors—affective repertoires and perceived language emotionality—in language choice of native Chukotkan parents, as a way of understanding human interactivity and the potential of the local environment for children’s acquisition of their heritage languages. Perceived language emotionality, I argue, is an important yet often overlooked aspect of heritage language sustainability and learning. The focus of this article is not on how bodies are transformed into objects of emotions (e.g., “the shamed one”), but on interplay between emotions and multilingual phenomena: how language and wordings are used to move people, to produce affects, attachments, equalities, and authenticities.